A debt to the revolution. Ways of studying the history of Portuguese anthropology - De Almeida, S. V.; Cachado, R. (Anthropologies, 2022)
The history of anthropology in Portugal began to be systematized after the Carnation Revolution of 1974, as a result of which the dictatorship fell in the country. In this article, we will look at how the history of Portuguese anthropology is studied. Several significant works have been published on this topic, as well as individual articles, thanks to which you can also understand the context. On the one hand, we will try to highlight the main ideas and subjects of discussions set forth in these works, and on the other hand, we will suggest possible ways for the development of Portuguese anthropology in the future.